2006
DOI: 10.1088/0957-4484/17/17/039
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of α-chitin whisker-reinforced poly(vinyl alcohol) nanocomposite nanofibres by electrospinning

Abstract: The present contribution reports, for the first time, the successful fabrication of α-chitin whisker-reinforced poly(vinyl alcohol) (PVA) nanocomposite nanofibres by electrospinning. The α-chitin whiskers were prepared from α-chitin flakes from shrimp shells by acid hydrolysis. The as-prepared chitin whiskers exhibited lengths in the range 231–969 nm and widths in the range 12–65 nm, with the average length and width being about 549 and 31 nm, respectively. Successful incorporation of the chitin whiskers withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(62 citation statements)
references
References 42 publications
1
60
0
1
Order By: Relevance
“…The nanocomposites of PVA and chitin whiskers were reported for the first time by Junkasem et al [170]. Nanowhiskers with the lengths in the range 231-969 nm and widths of 12 to 65 nm were produced.…”
Section: Chitin Nanowhiskersmentioning
confidence: 97%
“…The nanocomposites of PVA and chitin whiskers were reported for the first time by Junkasem et al [170]. Nanowhiskers with the lengths in the range 231-969 nm and widths of 12 to 65 nm were produced.…”
Section: Chitin Nanowhiskersmentioning
confidence: 97%
“…As-spun chitin nanofibers had the broad fiber diameter distribution showing that most of them are less than 100 nm [60]. Junkasem et al reported electrospinning of PVA and α-chitin whiskers prepared from shells of Penaeus merguiensis shrimps and produces nanofibrous mat for tissue engineering applications [61]. This investigation was carried out since both PVA had previously been electrospun [62] in water and chitin/PVA nanocomposite films containing α-chitin whiskers have also been fabricated in organic solvent system [63].…”
Section: Electrospinning Of Chitinmentioning
confidence: 99%
“…The studies have shown increase in tensile properties of nanocomposites for α-chitin whisker (ChW)/PVA (Junkasem et al 2006;Uddin et al 2012), α-ChW/ chitosan films (Sriupayo et al 2005), and α-ChW/soy protein isolate films (Lu et al 2004). In these studies an optimum ChW loading was reported, above which there was negligible improvement in these properties.…”
Section: Chistosan As Fillermentioning
confidence: 99%